2022
DOI: 10.20450/mjcce.2022.2491
|View full text |Cite
|
Sign up to set email alerts
|

Establishing mass spectral fragmentation patterns for characterization of 1,2 -unsaturated pyrrolizidine alkaloids and N-oxides in Boraginaceae species from Macedonia using LC-ESI-MS/MS

Abstract: Pyrrolizidine alkaloids (PAs) are secondary plant metabolites, and their 1,2-unsaturated derivatives, which contain the retronecine, heliotridine, or otonecine type of the necine base, have raised concern due to their ability to form hepatotoxic intermediates and exhibit serious toxic effects. Several hundred individual pyrrolizidine alkaloids and their N-oxides have been identified mostly using liquid chromatography coupled with mass spectrometry, although the number of available reference standards is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…According to the national Flora of Republic of Macedonia [11] the different plant species belong to Boraginaceae family are significantly widespread in the country and they are widely used in traditional medicine but up to date there are not available data about the presence and content of different classes of polyphenolic compounds. Our previously published studies [12,13] indicated that analyzed species contain low levels of pyrrolizidine alkaloids and they are not a health risk factor.…”
Section: Introductionmentioning
confidence: 94%
“…According to the national Flora of Republic of Macedonia [11] the different plant species belong to Boraginaceae family are significantly widespread in the country and they are widely used in traditional medicine but up to date there are not available data about the presence and content of different classes of polyphenolic compounds. Our previously published studies [12,13] indicated that analyzed species contain low levels of pyrrolizidine alkaloids and they are not a health risk factor.…”
Section: Introductionmentioning
confidence: 94%